Implementing Cisco Unified Communications Manager Part 1 (CIPT1) foundation learning guide : (CCNP Voice CIPT1 642-447) - Finke, Joshua; Hartmann, Dennis; Safari eBooks ([S.l.] : Cisco Systems, 2012)
"Implementing Cisco Unified Communications Manager, Part 1 (CIPT1) teaches you how to install and configure a Cisco Unified Communications Manager solution in a single site and focuses primarily on Cisco Unified Communications Manager Release v8.0, the call routing and signaling component for the Cisco Unified Communications solution. Topical coverage includes: CUCM deployment models, services, and installation, managing user accounts, single-site on-net calling, Cisco Catalyst switches, hardening IP phones, PSTN gateways, call routing, digit manipulation, calling privileges, call coverage, media resources, phone services, presence-enabled speed dials and lists, Cisco Unified Manager Assistant, and Cisco Unified Mobility. Each chapter ends with questions to help you assess your understanding of what you have read."--Resource description page.
Keywords: Communications software; Digital communications; Internet telephony; Electronic books